THE INFLUENCE OF POSTMODERNISM ON CONTEMPORARY MUSLIM THOUGHT - Dr. Ahmad Nadeem Chaudhry; Dr. Tariq Mahmood (International Journal of Contemporary Issues in Social Sciences, 2024)
The theory and ideology of postmodernism has changed the world, and very few areas of existence have been spared. Postmodernism (and the pluralism, skepticism, and relativism it produces) has altered how individuals create and perceive art, read and report the news, ponder and produce philosophical arguments, and perhaps most importantly, interpret and venerate spiritual texts, religion, and God. This paper focuses on the latter, and seeks to provide a broad overview of how postmodernism has changed Muslim thought in both positive and negative ways. In order to achieve this goal, we draw upon the writings of a diverse set of contemporary scholars, so as to provide a well-rounded understanding. The essay begins with a discussion on what exactly is meant by the term postmodernism. Following that, we explain how postmodernism has led to individuals viewing Muslims and Islamic practices differently. Next, we present some of the ways in which postmodernism has affected Islamic theology, including the rejection of a universal answer and the creation of new modes of interpretation. Subsequently, we discuss some of the fears some individuals have written about postmodernism (such as the theory creating indifference, apathy, and nihilism). After that, we explain how postmodernism has been associated with a rise in Islamic wave or Islamism. And lastly, we conclude the essay by presenting a model and standpoint of Islam that visually depicts the influence of postmodernism on followers of Islam.